2022
DOI: 10.1109/access.2022.3146419
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Circuits With a Real Non-Volatile Stanford Memristor Model

Abstract: Stanford memristor model is a widely used model that accurately characterizes real nonvolatile metal-oxide resistive random access memory (RRAM) devices with bipolar switching characteristics. The paper studies for the first time the dynamics and bifurcations in a class of nonlinear oscillators with real non-volatile memristor devices obeying Stanford model. This is in contrast with papers in the literature considering oscillators with ideal, abstract, or artificial memristor models, that are unable to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…7) CS of a NN, i.e., convergence of each trajectory toward an EP, is a peculiar dynamical property that can be guaranteed under suitable hypotheses on the activations and neuron interconnections (see Assumptions 1 and 2 in Theorem 1). On the other hand, in the general case, NNs do not enjoy CS since they can display sustained oscillations, traveling waves and even chaos and hyperchaos, see, e.g., [29], [59], [60], [61], [62], [63], [64], [65], [66], and references therein.…”
Section: Discussionmentioning
confidence: 99%
“…7) CS of a NN, i.e., convergence of each trajectory toward an EP, is a peculiar dynamical property that can be guaranteed under suitable hypotheses on the activations and neuron interconnections (see Assumptions 1 and 2 in Theorem 1). On the other hand, in the general case, NNs do not enjoy CS since they can display sustained oscillations, traveling waves and even chaos and hyperchaos, see, e.g., [29], [59], [60], [61], [62], [63], [64], [65], [66], and references therein.…”
Section: Discussionmentioning
confidence: 99%
“…where T is the temperature, v 0 , q, k, a 0 , ℓ, E ag , E ar , C th , R th , T 0 are given constants (see, e.g., [19]), and γ is a g-dependent local field enhancement factor, given by…”
Section: Symbol Unit Value Descriptionmentioning
confidence: 99%
“…Recently, it has been shown that modeling non-volatile memristors as programmable nonlinear resistors can be fruitfully exploited for the design of oscillatory circuits given by the interconnection of the memristor with a two-terminal linear element [19], [20]. A Chua's oscillatory circuit with a non-volatile extended memristor obeying Stanford model is designed in [19], showing via numerical simulations that it is capable to generate quite different coexisting dynamics. In [20] an oscillatory Chua's circuit based on a non-volatile memristive device is realized and its rich dynamical behavior is validated experimentally.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations